The Importance of Soft Skills for Accounting Students in Malaysia - Ismail, Suhaiza (Asian Journal of Accounting Perspectives, 2013)
This study empirically examines the importance of soft skills for accounting students in Malaysia. Survey questionnaires were distributed to 450 accounting students and practitioners. The total usable response rate for this study is 50.9%. The data were analysed using descriptive statistics including mean score, standard deviation, and ranking based on mean scores. The study found that the top three reasons for the importance of accounting graduates to acquire soft skills are ‘to provide high quality and professional services’, ‘to fulfil the expectation of employers’ and ‘to have better career prospects’. The findings imply that accounting students need to realize the importance of acquiring soft skills and actively equip themselves with soft skills demanded by the profession. The present study contributes to existing literature by offering empirical evidence on the importance of soft skills for future accountants, which is currently scarce.